Zweiter Offener Brief an Markus Henn (WEED) - Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2012)
Mehrere zivilgesellschaftliche Organisationen fordern ein Verbot bestimmter Finanzmarktspekulationen mit Agrarrohstoffen. Markus Henn (WEED) hat auf meinen Offenen Brief an ihn geantwortet. Auf diese Antwort, die hier im Anhang dokumentiert ist, reagiert mein Zweiter Offener Brief an ihn. Er begründet meine Lesart der ökonomischen Fachliteratur zum Thema sowie insbesondere meine These, dass die erhobenen Forderungen nach einer drastischen Einschränkung und sogar nach einem Verbot von Finanzmarktspekulationen mit Agrarrohstoffen den Mainstream der wissenschaftlichen Literatur nicht für sich, sondern gegen sich haben. – – Several civil-society organizations demand to outlaw specific financial market speculation with agricultural commodities. Markus Henn (WEED) responded to my Open Letter. His response is documented in the appendix. Here, I react with a Second Open Letter. It explains my interpretation of the economic literature on this topic. Specifically, it shows that the claim by civil society organizations to drastically reduce or even prohibit financial speculation with agricultural commodities is not supported by academic consensus and indeed runs against the mainstream of the scientific literature.
urn:nbn:de:gbv:3:2-17678
Keywords: 330; Agrarrohstoffe; Spekulation; Governance; Integrität; agricultural commodities; speculation; governance; integrity